Fold‐Sensitive Visible Fluorescence in β‐Sheet Peptide Structures. Issue 23 (18th March 2021) - Apter, Boris; Lapshina, Nadezda; Lapsker, Igor; Handelman, Amir; Accardo, Antonella; Diaferia, Carlo; Morelli, Giancarlo; Rosenman, Gil
Abstract: Fluorescence (FL) is a basic optical phenomenon that is widely used in molecular spectroscopy, high‐resolution microscopy, and bioimaging. It has exciting and emission spectra defined by an electronic structure of particular fluorochrome molecules. In this work, another type of FL is investigated. This FL phenomenon is observed both in biological amyloid and bioinspired amyloidogenic assemblies, folded into specific biomolecular β‐sheet secondary structure. A fine mechanism of this fold‐sensitive FL effect, arising at the earliest stages of seeding and nucleation of β‐sheet nanofibers, and its growth under thermally activated conformational refolding of helical to β‐sheet state in bioinspired ultrashort peptide structures are studied. This FL effect demonstrates different properties compared to the classical FL from non‐folded biomolecules or molecular dyes. Its excitation and emission spectra are similar in any β‐sheet peptide/protein assemblies irrespective of their biochemical composition, primary structure, and origin. It is shown that this fold‐sensitive FL effect exhibits a wideband spectrum, covering the entire visible region (400–650 nm), high quantum yield, and tunable FL wavelength. This research paves the way for advanced FL optical nanomaterials, for new methods of bioimaging and diagnostics as well as for the development of biocompatible nanoscale FL sources. Abstract : Visible fluorescence (FL) observed in β‐sheet amyloidogenic peptide/protein assemblies exhibits a wideband spectrum (400–650 nm) irrespective of their biochemical composition. This fold‐sensitive FL is revealed under helical to β‐sheet refolding at the earliest stages of the β‐sheet state nucleation and represents a universal technology for the transformation of non‐FL peptide/protein structures to the visible FL.